1997
DOI: 10.1002/(sici)1099-0801(199711)11:6<356::aid-bmc692>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective metabolic study of famprofazone

Abstract: Famprofazone (1) metabolites were studied in human urine after medication by 50 mg oral dose. The human urine was collected over 48 h from six volunteers at time intervals of 6, 12, 24 and 48 h. The amount of famprofazone metabolites were recovered from the urine samples by application of Extrelut extraction method. The resultant extracts were derivatized using N‐methyl‐N‐trimethylsilyltrifluoroacetamide (MSTFA) for trimethylsilylation followed by N‐methyl‐bis‐trifluoroacetamide (MBTFA) for trifluoroacetylatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Famprofazone is an analgesic that is metabolized to Dand L-MA (5% to 14% of dose excreted as MA) (Cody 1996;Neugebauer et al 1997;Tseng et al 2007); however, it is not approved for use in the USA and is considered an insignificant contributor to the MA in the study (Hope 2010). Benzphetamine in the form of Didrex is prescribed for obesity (Cloyd 1997;Cody and Valtier 1998;Stafford and Radley 2003) Utilization of Benzphetamine in Oregon is considered low because its use is greater among those with health insurance, and Oregon Medicaid (health insurance) has not approved amphetamines for weight loss (Hope 2010).…”
Section: Other Pharmaceuticals That Metabolize To Form Methamphetaminementioning
confidence: 99%
“…Famprofazone is an analgesic that is metabolized to Dand L-MA (5% to 14% of dose excreted as MA) (Cody 1996;Neugebauer et al 1997;Tseng et al 2007); however, it is not approved for use in the USA and is considered an insignificant contributor to the MA in the study (Hope 2010). Benzphetamine in the form of Didrex is prescribed for obesity (Cloyd 1997;Cody and Valtier 1998;Stafford and Radley 2003) Utilization of Benzphetamine in Oregon is considered low because its use is greater among those with health insurance, and Oregon Medicaid (health insurance) has not approved amphetamines for weight loss (Hope 2010).…”
Section: Other Pharmaceuticals That Metabolize To Form Methamphetaminementioning
confidence: 99%
“…Several studies have shown famprofazone is metabolized to methamphetamine and amphetamine (2)(3)(4)(5) and both the d-and l-enantiomers are present (2,3). One study observed the excretion rate for the first 24 h in 3 subjects after a single 50mg dose (6).…”
mentioning
confidence: 99%
“…3-hydroxymethyl-propyphenazone (3-OH-MP, m. wt. 246) was prepared in our laboratory by boiling, 1 g of 3-bromomethyl-propyphenazone in 50 ml water for 30 min [5] . The obtained crystals were washed with 0.1% sodium carbonate followed by water, filtered and dried over sodium hydroxide pellets in desiccators.…”
Section: Methodsmentioning
confidence: 99%